Effect of Effective Working Gap Position on Braking Performance of T-type Magnetorheological Brake - Yuming Huang; Jie Wu; Bingbing Deng (Jixie chuandong)
Aiming at the effect of different position and quantity working gaps of T-type magnetorheological（MR） brake on braking performance， combined with theoretical modeling and simulation analysis， the braking torque and magnetic field distribution of T-type magnetorheological brakes under different working states are studied under the constraints of the same size and the same magnetorheological fluid（MRF） material. Based on the different position and quantity of working gaps， the design of magnetic circuit and the theoretical modeling and calculation of braking torque are carried out. By comparing the simulation results with the theoretical calculation results， the braking torque generated by the working gaps at different positions is analyzed. The results show that when the MRF used in brake， the overall dimensions of consistent case， through the contrast of braking torque of the simulation analysis results and the theoretical calculation results， the relative difference in disc work condition is greater than the drum-type working state. Among them， under the disc working state， the relative difference of gap A is the largest， in the drum-type working state， the relative difference of gap D is the smallest. Furthermore， the braking torque generated by the gap D unit magnetomotive force is the largest， which indicates that this type of brake has the highest energy utilization rate under this working state. The research results provide a reference for the design and research of T-type magnetorheological brake.